Three Tuberculosis Spondylitis Patients With Resistant Rifampicin From the Transpedicular Debridement Surgery Network - Widowati, Yenny; Jane, Yani; Pratiwi, Suryanti Dwi; Asmiragani, Syaifullah (Malang Respiratory Journal, 2021)
Background: TB spondylitis is a disease that can cause neurological disorders, ranging from 1-2% of the total cases of tuberculosis where the most frequent infection is the spine followed by other large joints such as hips, knees and shoulders. The increase in TB spondylitis associated with MDR TB in 2015 showed 52% or about 32,000 incidences globally.Collaboration of individual alloy MDR TB therapy with surgery in TB spondylitis can reduce patient mortality and morbidity.Case: We report three cases of patients in 2017-2018 in Dr. Saiful Anwar with complaints of back pain and lumps in the back, from the results of anamnesa, physical examination and supporting examination of patients diagnosed with TB spondylitis, patients were given medical management, operative and rehabilitation.Conclusion: This case is interesting because from the results of Molecular Rapid Tests whose samples were obtained from a biopsy of the transpendicular debridement surgery tissue obtained the results of Resistant Rifampicin, all three patients received individualized OAT treatment, the development of the conditions of the three patients improved and quality of life improved.